Household labor supply and social protection: Evidence from Pakistan’s BISP cash transfer program - Ambler, Kate; de Brauw, Alan (International Food Policy Research Institute, 2019)
Cash transfers are a key component of social protection policy in many developing countries. Yet many policymakers are concerned that continued receipt of such transfers may have unintended consequences, such as a reduction in labor supply when household income rises. We study this question by evaluating the impact of Pakistan’s Benazir Income Support Program(BISP), a cash transfer program targeted to poor, married women,on male and female labor supply. The BISP was implemented via a mechanism that reliedon a poverty score cutoff to determine eligibility, allowing for the identification of causal impacts using regression discontinuity. We find no impacts on household labor supply in the aggregate. When we break up estimates by gender, we find littleevidence of a changein female labor supply, strongevidence of increased male labor supply, and no evidence of changes to child labor. Hence, policy makers should not be concerned that BISP transfers negatively affect labor supply among recipients.